Repaglinide/metformin fixed-dose combination to improve glycemic control in patients with type 2 diabetes: an update - Moses R (Dove Medical Press, 2010)
Robert G MosesClinical Trials and Research Unit, South East Sydney and Illawarra Area Health Service, New South Wales, AustraliaAbstract: Type 2 diabetes is a progressive disease associated with high levels of morbidity and mortality and for which there is both a large and growing prevalence worldwide. Lifestyle advice plus metformin is commonly recommended initially to manage hyperglycemia and to minimize the risk of vascular complications. However, additional agents are required when glycemic targets cannot be achieved or maintained due to the progressive nature of the disease. Repaglinide/metformin fixed-dose combination (FDC) therapy (PrandiMet®; Novo Nordisk, Bagsværd, Denmark) has been approved for use in the USA. This FDC is a rational second-line therapy given the complementary mechanisms of action of the components. Repaglinide is a rapidly absorbed, short-acting insulin secretagogue targeting postprandial glucose excursions; metformin is an insulin sensitizer with a longer duration of action that principally regulates basal glucose levels. A pivotal, 26-week, randomized study with repaglinide/metformin FDC therapy has been conducted in patients experiencing suboptimal control with previous oral antidiabetes therapy. Repaglinide/metformin FDC improved glycemic control and weight neutrality without adverse effects on lipid profiles. There were no major hypoglycemic episodes and patients expressed greater satisfaction with repaglinide/metformin FDC than previous treatments. Repaglinide/metformin FDC is expected to be more convenient than individual tablets for patients taking repaglinide and metformin in loose combination, and it is expected to improve glycemic control in patients for whom meglitinide or metformin monotherapies provide inadequate control.Keywords: type 2 diabetes, metformin, repaglinide, PrandiMet®, fixed-dose combination